Effect of two desensitizing agents on dentin permeability in vitro - Hiroshi ISHIHATA; Masafumi KANEHIRA; Werner J. FINGER; Hidekazu TAKAHASHI; Makoto TOMITA; Keiichi SASAKI
Abstract Objective The aim of this in vitro study was to investigate the effect of two desensitizing agents and water on hydraulic conductance in human dentin. Material and Methods GLUMA Desensitizer PowerGel (GLU) contains glutaraldehyde (GA) and 2-hydroxyethyl methacrylate (HEMA), and Teethmate Desensitizer (TD) is a powder comprising tetracalcium phosphate (TTCP) and dicalcium phosphate anhydrous (DCPA) that is mixed with water. Deionized water was used as a negative control (CTR). Thirty discs with a thickness of 1.2 mm were cut from the coronal dentin of the third molars and cleaned with 0.5 M EDTA (pH 7.4). After being mounted in a split-chamber device, the discs were pressurized with water at 1 kPa and 3 kPa in order to measure flow rates with a highly sensitive micro-flow sensor and to calculate hydraulic conductance as a baseline value (BL). Following the application of GLU, TD, and CTR (n=10), hydraulic conductance was remeasured with intermittent storage in water after 15 min, 1 d, 1 w, and 1 m. Reduction in permeability (PR%) was calculated from hydraulic conductance. Data were statistically analyzed using nonparametric methods (α<0.05). Representative discs were inspected by SEM. Results PR% for GLU and TD were 30-50% 15 min and 1 m after their application. Post hoc tests indicated that PR% of CTR was significantly greater than those of GLU and TD at all time points tested. The PR% of GLU and TD were not significantly different. SEM examinations showed noncollapsed collagen meshes at the tubular entrances after GLU, and crystalline precipitates occluding the tubular orifices after TD, whereas CTR specimens showed typical patterns of etched dentin. Conclusions The present study on hydraulic conductance in dentin discs treated with two chemically different desensitizing agents and water as a control demonstrated that both products may be characterized as effective.